2022
DOI: 10.3390/land11020208
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Environmental Variables and Their Interactions on Chinese Farmland Soil Organic Carbon Density and Its Dynamics

Abstract: Farmland is one of the most important and active components of the soil carbon pool. Exploring the controlling factors of farmland soil organic carbon density (SOCD) and its sequestration rate (SOCDSR) is vital for improving carbon sequestration and addressing climate change. Present studies provide considerable attention to the impacts of natural factors and agricultural management on SOCD and SOCDSR. However, few of them focus on the interaction effects of environmental variables on SOCD and SOCDSR. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Variability in soil carbon can be attributed to differences in farm management and fertilization strategies as different parts of the coffee farm are intercropped with seasonal crops during rainy seasons. This observation agrees with the findings of Zhao et al (2021), Li et al (2021) Jakši´et al (2021 and Wu et al (2022), who identified heterogeneity of soil carbon in studied fields.…”
Section: Organic Carbon (%Oc)supporting
confidence: 93%
See 1 more Smart Citation
“…Variability in soil carbon can be attributed to differences in farm management and fertilization strategies as different parts of the coffee farm are intercropped with seasonal crops during rainy seasons. This observation agrees with the findings of Zhao et al (2021), Li et al (2021) Jakši´et al (2021 and Wu et al (2022), who identified heterogeneity of soil carbon in studied fields.…”
Section: Organic Carbon (%Oc)supporting
confidence: 93%
“…(2021) Jakši´et al. (2021) and Wu et al. (2022) , who identified heterogeneity of soil carbon in studied fields.…”
Section: Resultsmentioning
confidence: 97%
“…Zhang et al (2022) found that the SOC content of farmland in each geographical area of China was lower than that of grassland and forest land. Although temperature and precipitation would also affect the formation and evolution of SOC in forest land, grassland and wetland, SOC in farmland had certain uniqueness (Wu et al 2022). Farmland ecosystem carbon pool was the most active part of the global carbon pool.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the significance of SOC stocks' drivers in agricultural ecosystems, Funes et al (2019) used geographically weighted regression and generalized least squares analysis, demonstrating that the main determinants of topsoil variance in SOC stores were the climate and agricultural factors. With 64 samples taken from 19 agricultural sites around China, SOC storage for cropland ecosystems was connected to natural parameters such as MAT, soil type, clay content, and MAP (Wu et al, 2022). These studies elucidate an inconsistency in the drivers of SOC, which is likely due to inconsistencies in the factors selected and being limited to specific ecosystem.…”
Section: Introductionmentioning
confidence: 99%